Preparation method of catalyst for hydrogenation of organic liquid hydrogen storage medium, catalyst and application thereof, and hydrogenation method of dibenzyltoluene

By using hydrothermal crystallization and impregnation methods to prepare catalysts during the hydrogen storage process of liquid organic matter, the problems of poor stability and insufficient hydrogenation rate of the hydrogenation catalyst are solved, and the ultra-long life and efficient hydrogenation effect of the catalyst are achieved.

CN118874476BActive Publication Date: 2025-02-28BEIJING HYWIN HYDROGEN ENERGY TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411369618.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-02-28
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

In the prior art, the hydrogenation catalyst has poor stability and insufficient hydrogenation rate during the hydrogen storage process of liquid organic matter, resulting in a low catalyst life and a decrease in activity caused by the aggregation of metal particles.

Method used

By adopting a preparation method, a mixed solution containing a first active metal source, an ammonium salt and a base is prepared and hydrothermal crystallized with an alumina support to form a catalyst intermediate, and then the second active metal is supported by an impregnation method, and calcined and reduced treatment is carried out under a reducing atmosphere to obtain a catalyst with high catalytic activity and stability.

Benefits of technology

The prepared catalyst exhibits ultra-long life and good industrial applicability during the hydrogenation process of liquid organic matter. Through hydrothermal crystallization and the formation of nano alloy structures, metal particles aggregation is avoided and hydrogenation efficiency is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of catalyst preparation, and discloses a preparation method of a catalyst for hydrogenation of an organic liquid hydrogen storage medium, a catalyst and its application, and a method for hydrogenation of dibenzyltoluene. The preparation method comprises: (1) preparing a mixed solution containing a first active metal source, an ammonium salt and an alkali; (2) mixing the mixed solution with an alumina carrier; (3) hydrothermally crystallizing the product obtained in step (2), and then drying and first calcining to obtain a catalyst intermediate; (4) loading a second active metal on the catalyst intermediate by an impregnation method, and then performing a second calcination; (5) reducing the product of the second calcination under a reducing atmosphere; wherein the first active metal is selected from nickel and / or cobalt, and the second active metal is selected from at least one of gallium, indium and tin. The catalyst prepared by the method has high catalytic activity and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalyst preparation, and in particular to a preparation method of a catalyst for hydrogenating an organic liquid hydrogen storage medium, a catalyst and application thereof, and a dibenzyltoluene hydrogenation method. Background Art

[0002] Hydrogen energy is a clean and efficient energy source that is widely used in various fields, such as automobiles and electricity production. However, the storage of hydrogen is an important challenge. At present, the main hydrogen storage methods include high-pressure gas storage, low-temperature liquid storage, and solid material storage. Traditional high-pressure gas storage has little room for further development due to low energy density, safety hazards, high container costs, and limited infrastructure. In contrast, the emerging liquid organic hydrogen storage technology has broad application prospects in the field of hydrogen energy due to its advantages such as high hydrogen storage density, liquid stability, high safety, use of existing infrastructure, and recyclability. In addition, due to the strong operational flexibility of liquid organic hydrogen storage technology, it can be coupled with upstream wind and solar power generation to convert discontinuous intermittent electricity into continuous and stable output of electricity resources, effectively solving the problem of wind and solar power abandonment. In addition, due to its excellent operational flexibility, liquid organic hydrogen storage technology can be closely combined with upstream wind and solar power generation to convert the originally discontinuous intermittent electricity into continuous and stable power output, thereby effectively solving the problem of power abandonment generated during wind and solar power generation.

[0003] The realization of liquid organic hydrogen storage technology depends on efficient hydrogenation and dehydrogenation catalysts. In order to achieve efficient liquid organic hydrogen storage at low cost, the scientific research community and the industrial community often choose Ni and Co with high hydrogenation activity as active metals. Although the two elements have certain activity in the hydrogenation reaction of N-heterocyclic compounds, they often have problems such as low hydrogenation rate, poor thermal stability, and easy aggregation of particles. Especially for traditional oxide carriers, their chemical and mechanical strength often weakens with the progress of hydrogenation reaction, and the life of the catalyst is low. On the other hand, metal nanocatalysts often suffer from decreased activity caused by particle aggregation during operation.

[0004] Therefore, although traditional hydrogenation catalysts have been widely used in many industrial processes, their operating stability often cannot achieve ideal results in the hydrogenation reaction of liquid hydrogen storage materials. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems of poor stability and insufficient hydrogenation rate of hydrogenation catalysts with liquid organic hydrogen storage in the prior art, and to provide a preparation method of a catalyst for hydrogenation of an organic liquid hydrogen storage medium, a catalyst and its application, and a method for hydrogenating dibenzyltoluene. The catalyst prepared by the preparation method has high catalytic activity and good operating stability.

[0006] In order to achieve the above object, the present invention provides a method for preparing a catalyst for hydrogenation of an organic liquid hydrogen storage medium, comprising:

[0007] (1) preparing a mixed solution containing a first active metal source, an ammonium salt and an alkali;

[0008] (2) mixing the mixed solution with an alumina carrier;

[0009] (3) subjecting the product obtained in step (2) to hydrothermal crystallization, followed by drying and first calcination to obtain a catalyst intermediate;

[0010] The conditions of the hydrothermal crystallization include: a temperature of 80-140°C and a time of 24-72h;

[0011] (4) loading a second active metal onto the catalyst intermediate by an impregnation method, and then performing a second calcination;

[0012] (5) subjecting the second calcined product to a reduction treatment under a reducing atmosphere;

[0013] Wherein, the first active metal is selected from nickel and / or cobalt, and the second active metal is selected from at least one of gallium, indium and tin.

[0014] The second aspect of the present invention provides a catalyst prepared by the above-mentioned method for preparing a catalyst for hydrogenation of an organic liquid hydrogen storage medium.

[0015] The third aspect of the present invention provides use of the catalyst described in the second aspect in organic liquid hydrogen storage.

[0016] A fourth aspect of the present invention provides a method for hydrogenating dibenzyltoluene, comprising: contacting dibenzyltoluene with a hydrogenation catalyst in the presence of hydrogen under hydrogenation reaction conditions;

[0017] Wherein, the hydrogenation catalyst is the catalyst described in the second aspect.

[0018] The preparation method provided by the present invention comprises the following steps: firstly mixing a mixed solution containing a first active metal source, an ammonium salt and an alkali with an alumina carrier and then performing hydrothermal crystallization to obtain a catalyst intermediate, and then loading a second active metal by an impregnation method. The catalyst obtained after calcination and reduction has high catalytic activity and stability, and exhibits an ultra-long life in the process of hydrogenation of liquid organic matter, and has good industrial applicability. The reason for this may be that during the hydrothermal crystallization process, the first active metal forms a corresponding active metal hydrotalcite precursor on the surface of the alumina carrier, which can enhance the binding force between the first active metal and the carrier, and is conducive to the first active metal and the second active metal forming nano alloy particles riveted on the formed alumina carrier, thereby obtaining highly dispersed hydrogenation sites.

[0019] In addition, the present invention omits the traditional catalyst molding step and directly uses the molded alumina as a carrier to prepare the catalyst, which has multiple advantages such as simplifying the production process, reducing production costs, and improving industrial applicability. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a high-resolution transmission electron micrograph of the catalyst CAT-1 prepared in Example 1. DETAILED DESCRIPTION

[0021] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0022] The first aspect of the present invention provides a method for preparing a catalyst for hydrogenating an organic liquid hydrogen storage medium, comprising:

[0023] (1) preparing a mixed solution containing a first active metal source, an ammonium salt and an alkali;

[0024] (2) mixing the mixed solution with an alumina carrier;

[0025] (3) subjecting the product obtained in step (2) to hydrothermal crystallization, followed by drying and first calcination to obtain a catalyst intermediate;

[0026] The conditions of the hydrothermal crystallization include: a temperature of 80-140°C and a time of 24-72h;

[0027] (4) loading a second active metal onto the catalyst intermediate by an impregnation method, and then performing a second calcination;

[0028] (5) subjecting the second calcined product to a reduction treatment under a reducing atmosphere;

[0029] Wherein, the first active metal is selected from nickel and / or cobalt, and the second active metal is selected from at least one of gallium, indium and tin.

[0030] In the prior art, the preparation of hydrogenation catalysts usually adopts traditional preparation methods such as impregnation method or precipitation method. However, the inventors of the present invention have found in their research that the hydrogenation catalysts prepared by the traditional preparation methods have problems such as low hydrogenation rate, poor thermal stability, and easy aggregation of particles in liquid organic hydrogen storage. Especially for traditional oxide carriers, their chemical and mechanical strengths often weaken as the hydrogenation reaction proceeds, and the life of the catalyst is relatively low. On the other hand, metal nanocatalysts often suffer from decreased activity caused by particle aggregation during operation.

[0031] Compared with the existing preparation method, the catalyst prepared by the preparation method of the present invention has higher catalytic activity and stability, and exhibits an ultra-long life in the process of hydrogenation of liquid organic matter, and has good industrial applicability. The reason for this may be that during the hydrothermal crystallization process, the first active metal forms a corresponding active metal hydrotalcite precursor on the surface of the alumina carrier, which can enhance the binding force between the first active metal and the carrier, and then the second active metal is introduced by the impregnation method, which is conducive to the first active metal and the second active metal forming nano alloy particles riveted on the molded alumina carrier, thereby obtaining highly dispersed hydrogenation sites, which not only enhances the bonding strength between the active metal and the carrier, but also greatly avoids the aggregation of metal particles during the hydrogenation process.

[0032] In the present invention, the first active metal is nickel and / or cobalt. It is understood that the first active metal may be nickel, or the first active metal is cobalt, or the first active metal includes nickel and cobalt. When the first active metal includes nickel and cobalt, nickel and cobalt may be combined in any proportion, preferably, the molar ratio of nickel to cobalt is 0.5-2:1.

[0033] The present invention has a wide selection range for the ammonium salt and the base, which can be conventionally selected in the art.

[0034] According to some preferred embodiments of the present invention, the ammonium salt is selected from ammonium chloride and / or ammonium nitrate.

[0035] According to some preferred embodiments of the present invention, the base is urea.

[0036] Preferably, the molar ratio of the ammonium salt to the base is 1.5-2.5:1, for example, it can be a specific but non-limiting molar ratio of 1.5:1, 2:1, 2.5:1, etc.

[0037] According to some preferred embodiments of the present invention, the molar ratio of the base to the metal element in the first active metal source is (2-20):1, preferably, the molar ratio of the base to the metal element in the first active metal source is (5-15):1, for example, it can be 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1 and other specific but non-limiting molar ratios or any range between the two. The above preferred embodiments are adopted to facilitate the active metal ions to be fully precipitated and to grow uniformly during the hydrothermal process, further improving the catalytic activity of the prepared catalyst.

[0038] According to the present invention, the mixed solution further contains a solvent. The present invention has a wide range of choices for the type of the solvent, as long as it can dissolve the above components. For example, the solvent may be water.

[0039] The present invention has no particular limitation on the amount of the solvent, which is also based on the ability to fully dissolve and disperse the above components. Preferably, the amount of the solvent is such that the concentration of the first active metal source in the mixed solution is 0.05-0.5 mol / L, preferably 0.1-0.4 mol / L.

[0040] In the present invention, the alumina carrier is a shaped carrier. By mixing the mixed solution with the alumina carrier and then performing hydrothermal crystallization, a coating structure of a hydrotalcite precursor containing a first active metal can be formed on the surface of the alumina carrier, which is beneficial to enhancing the binding force between the carrier and the active metal and the dispersion of the active metal. At the same time, the present invention directly uses the shaped alumina as a carrier to prepare the catalyst, which can omit the traditional catalyst molding step.

[0041] In the present invention, the alumina carrier can be prepared by conventional methods in the art, or can be obtained commercially. The present invention has no particular limitation on the shape of the alumina carrier, which can be at least one of a columnar, a cloverleaf, a toothed ball, and a spherical shape, and those skilled in the art can select according to actual needs.

[0042] In the present invention, the mixing in step (2) can be performed in any mixing device, as long as the mixed solution and the alumina support are fully and evenly mixed without destroying the morphology of the alumina support.

[0043] According to some preferred embodiments of the present invention, the mixing in step (2) is performed in a coating machine. The above preferred embodiments are advantageous for achieving uniform mixing while keeping the shaped carrier intact.

[0044] According to the invention, preferably, the rotation speed of the coating machine is 40-100 rpm, preferably 60-80 rpm, and the mixing time is 2-4 hours. The above preferred embodiment is advantageous for further improving the catalytic activity of the prepared catalyst.

[0045] According to some preferred embodiments of the present invention, the mass ratio of the first active metal in the mixed solution to the alumina support is (5-25): 100, preferably (6-23): 100. Controlling the amount of both within the above preferred range is conducive to increasing the component content and inhibiting the aggregation of metal particles after reduction, further improving the catalytic activity of the prepared catalyst.

[0046] In the present invention, the hydrothermal crystallization in step (3) is carried out by controlling the temperature to 80-150°C and the time to 24-72h, so that the mixed solution forms a hydrotalcite precursor containing the first active metal on the surface of the alumina carrier. The hydrothermal crystallization can be carried out under the pressure of the hydrothermal autoclave itself, and the present invention has no particular limitation on this. Preferably, the conditions of the hydrothermal crystallization include: a temperature of 90-140°C and a time of 36-48h. Under the above preferred conditions, it is beneficial to ensure the crystallinity of the catalyst precursor and further improve the catalytic activity of the obtained catalyst.

[0047] According to the present invention, preferably, the hydrothermal crystallization is carried out under closed conditions, and can be carried out in any conventional reaction device that can be used for hydrothermal synthesis in the art, for example, a hydrothermal autoclave with polytetrafluoroethylene.

[0048] According to the present invention, preferably, the first calcination is performed in the presence of oxygen, and the oxygen can be provided by air.

[0049] Preferably, the temperature of the first calcination is 350-650°C, preferably 400-600°C; the time is 1-10h, preferably 2-8h.

[0050] According to the present invention, preferably, in step (4), the mass ratio of the loading amount of the second active metal to the first active metal in the catalyst intermediate is (0.1-0.6):1, preferably (0.2-0.4):1. Controlling the loading amount of the first active metal and the second active metal within the above range is conducive to forming a uniform nano-alloy structure catalyst and further improving the catalytic effect of the prepared catalyst.

[0051] According to the present invention, preferably, in step (4), the method of loading the second active metal onto the catalyst intermediate by impregnation comprises: contacting a solution containing a soluble compound of the second active metal with the catalyst intermediate. The impregnation method may be an isovolumetric impregnation method.

[0052] According to the present invention, preferably, in the solution containing the soluble compound of the second active metal, the concentration of the soluble compound of the second active metal calculated as the metal element is 2-18 wt %.

[0053] Preferably, the second calcination is performed in the presence of oxygen, which may be provided by air.

[0054] Preferably, the second calcination is carried out at a temperature of 400-600° C., preferably 450-550° C., for a time of 4-6 h, preferably 5-5.5 h.

[0055] According to the present invention, preferably, the reducing atmosphere is a hydrogen-containing atmosphere, and the hydrogen-containing atmosphere may be hydrogen or a mixture of hydrogen and an inert gas. Preferably, the concentration of hydrogen in the hydrogen-containing atmosphere is 5-100 vol%. The inert gas may be nitrogen and / or argon.

[0056] Preferably, the reduction treatment temperature is 500-800° C., and the reduction time is 2-8 hours.

[0057] According to some preferred embodiments of the present invention, the first active metal source, the second active metal and the alumina carrier are used in such amounts that, based on the total amount of the prepared catalyst, the content of the alumina carrier is 70-98wt%, preferably 72-94wt%; the content of the first active metal is 3-20wt%, preferably 5-18wt%; the content of the second active metal is 0.5-11wt%, preferably 1-10wt%. When the prepared catalyst is composed of the alumina carrier, the first active metal and the second active metal, the sum of the contents of the three satisfies 100%.

[0058] In the present invention, the composition of each component in the catalyst is obtained by testing using an inductively coupled plasma atomic emission spectroscopy (ICP-AES) method.

[0059] The second aspect of the present invention provides a catalyst prepared by the above-mentioned method for preparing a catalyst for hydrogenation of an organic liquid hydrogen storage medium.

[0060] Preferably, the catalyst comprises an alumina carrier and a first active metal and a second active metal supported on the alumina carrier, the first active metal being selected from nickel and / or cobalt, and the second active metal being selected from at least one of gallium, indium and tin.

[0061] In the present invention, the first active metal and the second active metal exist in the form of an alloy, and the existence of the alloy structure can be characterized by a high-resolution transmission electron microscope.

[0062] The third aspect of the present invention provides the use of the above catalyst in organic liquid hydrogen storage.

[0063] A fourth aspect of the present invention provides a method for hydrogenating dibenzyltoluene, comprising: contacting dibenzyltoluene with a hydrogenation catalyst in the presence of hydrogen under hydrogenation reaction conditions;

[0064] Wherein, the hydrogenation catalyst is the catalyst described in the second aspect.

[0065] According to the present invention, preferably, the hydrogenation reaction conditions include: temperature of 120-180°C, preferably 140-170°C, pressure of 6-14MPa, preferably 8-14MPa, volume ratio of dibenzyltoluene to hydrogen of 1:(2000-4000), preferably 1:(3000-3500), volume space velocity of dibenzyltoluene of 0.02-0.1h -1 , preferably 0.04-0.08h -1 .

[0066] The present invention will be described in detail below through examples.

[0067] Example 1

[0068] (1) Weigh 11.64 g nickel nitrate hexahydrate, 24 g urea and 10.67 g ammonium chloride and dissolve them in 200 g deionized water, and stir to form a salt solution;

[0069] (2) The salt solution was transferred to a coating machine, and 20 g of γ-alumina balls with a diameter of 2-4 nm were added, and the mixture was rotated and mixed at 70 rpm for 2 hours in the coating machine;

[0070] (3) The obtained solid-liquid mixture was transferred into a hydrothermal reactor with polytetrafluoroethylene and hydrothermally crystallized at 110 °C for 48 hours to obtain a shaped tooth ball-hydrotalcite precursor; the obtained precursor was washed three times with deionized water, dried in an oven at 90 °C overnight, and then calcined in a muffle furnace at 500 °C for 5 hours;

[0071] (4) 3.45 g of hydrated gallium nitrate was dissolved in 10 g of deionized water, and the calcined molded support was impregnated into the gallium nitrate solution, and then calcined in a muffle furnace at 550 °C for 5.5 h to obtain a catalyst precursor;

[0072] (5) The catalyst precursor was placed in a hydrogen atmosphere and reduced at 750 °C for 4 h to obtain a formed NiGa alloy catalyst CAT-1. The catalyst composition was analyzed by ICP-AES, and the results are shown in Table 1.

[0073] The catalyst CAT-1 was analyzed by high-resolution transmission electron microscopy. Figure 1 As shown, it can be seen that stripes belonging to the Ni3Ga1(111) crystal plane appear, indicating that intermetallic compound nanoparticles with good crystal form are formed.

[0074] Example 2

[0075] Preparation of catalyst:

[0076] (1) Weigh 5.82 g of nickel nitrate hexahydrate, 18 g of urea, and 13 g of ammonium nitrate and dissolve them in 200 g of deionized water. Stir well to form a salt solution.

[0077] (2) The salt solution was transferred to a coating machine, and 20 g of γ-alumina spheres with a diameter of 1-2 nm were added, and the mixture was rotated and mixed at 60 rpm in the coating machine for 2 hours;

[0078] (3) The obtained solid-liquid mixture was transferred into a hydrothermal reactor with polytetrafluoroethylene, and hydrothermally crystallized at 90 °C for 72 hours to obtain a shaped spherical hydrotalcite precursor; the obtained precursor was washed three times with deionized water, dried in an oven at 90 °C overnight, and then calcined in a muffle furnace at 450 °C for 6 hours;

[0079] (4) dissolving 0.65 g of hydrated indium nitrate in 10 g of deionized water, impregnating the calcined shaped carrier into the indium nitrate solution, and then calcining in a muffle furnace at 500 °C for 5 h to obtain a catalyst precursor;

[0080] (5) The catalyst precursor was placed in a hydrogen atmosphere and reduced at 700 °C for 5 h to obtain a formed NiIn alloy catalyst CAT-2. The catalyst composition was analyzed by ICP-AES, and the results are shown in Table 1.

[0081] Example 3

[0082] (1) Dissolve 23.28 g of nickel nitrate hexahydrate, 24 g of urea and 10.67 g of ammonium chloride in 200 g of deionized water and stir to form a salt solution;

[0083] (2) The salt solution was transferred to a coating machine, and 20 g of columnar γ-alumina with a diameter of 3 mm and a length of 5 mm was added, and the mixture was mixed at 80 rpm in the coating machine for 2 hours;

[0084] (3) The obtained solid-liquid mixture was transferred into a hydrothermal reactor with polytetrafluoroethylene, and hydrothermally crystallized at 140 °C for 24 hours to obtain a columnar hydrotalcite precursor; the obtained precursor was washed three times with deionized water, dried in an oven at 90 °C overnight, and then calcined in a muffle furnace at 550 °C for 4 hours;

[0085] (4) Dissolve 6.18 g of tin tetrachloride in 10 g of dilute hydrochloric acid, immerse the calcined molded support into the tin tetrachloride solution, and then calcine in a muffle furnace at 550 °C for 4 h to obtain a catalyst precursor;

[0086] (5) The catalyst precursor was placed in a hydrogen atmosphere and reduced at 600 °C for 7 h to obtain a formed NiSn alloy catalyst CAT-3. The catalyst composition was analyzed by ICP-AES, and the results are shown in Table 1.

[0087] Example 4

[0088] (1) Weigh 11.64 g nickel nitrate hexahydrate, 24 g urea and 10.67 g ammonium chloride and dissolve them in 200 g deionized water, and stir to form a salt solution;

[0089] (2) The salt solution was transferred to a coating machine and 20 g of clover gamma-alumina with a diameter of 2 mm and a length of 4 mm was added. The mixture was mixed at 40 rpm in the coating machine for 2 hours.

[0090] (3) The obtained solid-liquid mixture was transferred into a hydrothermal reactor with polytetrafluoroethylene, and hydrothermally crystallized at 90 °C for 48 hours to obtain a shaped clover-hydrotalcite precursor; the obtained precursor was washed three times with deionized water, dried in an oven at 90 °C overnight, and then calcined in a muffle furnace at 400 °C for 8 hours;

[0091] (4) dissolving 3.45 g of hydrated gallium nitrate in 10 g of deionized water, impregnating the calcined shaped support into the gallium nitrate solution, and then calcining in a muffle furnace at 450 °C for 6 h to obtain a catalyst precursor;

[0092] (5) The catalyst precursor was placed in a hydrogen atmosphere and reduced at 500 °C for 8 h to obtain a formed NiGa alloy catalyst CAT-4. The catalyst composition was analyzed by ICP-AES, and the results are shown in Table 1.

[0093] Example 5

[0094] (1) Weigh 11.64 g of cobalt nitrate hexahydrate, 24 g of urea, and 10.67 g of ammonium chloride and dissolve them in 200 g of deionized water. Stir well to form a salt solution.

[0095] (2) The salt solution was transferred to a coating machine, and 20 g of γ-alumina balls with a diameter of 2-4 nm were added, and the mixture was rotated and mixed at 100 rpm for 2 hours in the coating machine;

[0096] (3) The obtained solid-liquid mixture was transferred into a hydrothermal reactor with polytetrafluoroethylene and hydrothermally crystallized at 110 °C for 48 hours to obtain a tooth ball-hydrotalcite precursor; the obtained precursor was washed three times with deionized water, dried in an oven at 90 °C overnight, and then calcined in a muffle furnace at 600 °C for 2 hours;

[0097] (4) dissolving 3.45 g of hydrated gallium nitrate in 10 g of deionized water, impregnating the calcined shaped support into the gallium nitrate solution, and then calcining in a muffle furnace at 500 °C for 5 h to obtain a catalyst precursor;

[0098] (5) The catalyst precursor was placed in a hydrogen atmosphere and reduced at 800 °C for 2 h to obtain a formed CoGa alloy catalyst CAT-5. The catalyst composition was analyzed by ICP-AES, and the results are shown in Table 1.

[0099] Example 6

[0100] (1) Weigh 5.82 g of nickel nitrate hexahydrate, 5.82 g of cobalt nitrate hexahydrate, 24 g of urea and 10.67 g of ammonium chloride and dissolve them in 200 g of deionized water, and stir to form a salt solution;

[0101] (2) The salt solution was transferred to a coating machine, and 20 g of γ-alumina balls with a diameter of 2-4 nm were added, and the mixture was rotated and mixed at a speed of 70 rpm for 2 hours in the coating machine to obtain an alumina mixed solution;

[0102] (3) The solid-liquid mixed solution was transferred into a hydrothermal reactor with polytetrafluoroethylene, and hydrothermally crystallized at 110 °C for 48 hours to obtain a tooth ball-hydrotalcite precursor; the obtained precursor was washed three times with deionized water, dried in an oven at 90 °C overnight, and then calcined in a muffle furnace at 450 °C for 3 hours;

[0103] (4) dissolving 3.45 g of hydrated gallium nitrate in 10 g of deionized water, impregnating the calcined shaped support into the gallium nitrate solution, and then calcining in a muffle furnace at 550 °C for 5 h to obtain a catalyst precursor;

[0104] (5) The catalyst precursor was placed in a hydrogen atmosphere and reduced at 550 °C for 6 h to obtain a formed NiCoGa alloy catalyst CAT-6. The catalyst composition was analyzed by ICP-AES, and the results are shown in Table 1.

[0105] Example 7

[0106] The method of Example 1 is followed, except that in step (3), the temperature of hydrothermal crystallization is 80° C. and the time is 24 h.

[0107] The obtained catalyst was recorded as CAT-7. The catalyst composition was analyzed by ICP-AES, and the results are shown in Table 1.

[0108] Example 8

[0109] The method of Example 1 was followed, except that the amount of hydrated gallium nitrate was 0.2 g. The obtained catalyst was recorded as CAT-8. The catalyst composition was analyzed by ICP-AES, and the results are shown in Table 1.

[0110] Comparative Example 1

[0111] The method of Example 1 was followed, except that step (4) was not performed, and the intermediate obtained in step (3) was directly reduced. The obtained catalyst was recorded as DCAT-1. The catalyst composition was analyzed by ICP-AES, and the results are shown in Table 1.

[0112] Comparative Example 2

[0113] (1) Weigh 11.64 g of nickel nitrate hexahydrate, 30.0 g of aluminum nitrate nonahydrate, 24 g of urea and 10.67 g of ammonium chloride and dissolve them in 200 g of deionized water, and stir them to form a salt solution; transfer the salt solution to a hydrothermal reactor with polytetrafluoroethylene, and perform hydrothermal crystallization at 110 °C for 48 hours to obtain non-solidified NiAl hydrotalcite;

[0114] (2) The green precipitate was washed three times with deionized water, dried in an oven at 90 °C overnight, and then calcined in a muffle furnace at 500 °C for 5 h;

[0115] (3) dissolving 3.45 g of hydrated gallium nitrate in 10 g of deionized water, immersing the calcined solid powder in the gallium nitrate solution, and then calcining in a muffle furnace at 550 °C for 5.5 h to obtain a catalyst precursor;

[0116] (4) placing the catalyst precursor in a hydrogen atmosphere and reducing it at 750 °C for 4 h to obtain a powdered NiGa alloy catalyst;

[0117] (5) The powder catalyst was mixed with a dilute nitric acid solution, kneaded in a kneader for 30 min, and extruded into strips using a twin-screw extruder to obtain a shaped NiGa alloy catalyst DCAT-2. The catalyst composition was analyzed by ICP-AES. The results are shown in Table 1.

[0118] Comparative Example 3

[0119] 11.64 g of nickel nitrate hexahydrate and 3.45 g of hydrated gallium nitrate were weighed and dissolved in 25 g of deionized water, 20 g of γ-alumina tooth balls with a diameter of 2-4 nm were impregnated into the above solution, dried in a 90 °C oven overnight, and then calcined in a muffle furnace at 500 °C for 5 h to obtain a catalyst precursor; the catalyst precursor was placed in a hydrogen atmosphere and reduced at 750 °C for 4 h to obtain a formed NiGa alloy catalyst DCAT-3. The catalyst composition was analyzed by ICP-AES, and the results are shown in Table 1.

[0120] Table 1

[0121]

[0122] Test Case

[0123] 1 L of shaped catalyst particles was loaded into the fixed bed reactor, and hydrogen was introduced; after the temperature and pressure were increased, the liquid hydrogen storage material dibenzyltoluene was transported to the reactor by a high-pressure pump and mixed with hydrogen in a preheating furnace; the reaction products were separated in a gas-liquid separation tank, the liquid was sampled and analyzed, and the tail gas was pressurized by a compressor for recycling. The products within the first 12 hours of the reaction were discarded, and the component content was sampled and analyzed every 1 hour thereafter, and the conversion rate and hydrogen storage rate were calculated. The results are shown in Table 2.

[0124] in,

[0125] Hydrogenation rate (%) = ;

[0126] Mass hydrogen storage rate (wt%) = .

[0127] Table 2

[0128]

[0129] From the comparison of the above examples and comparative examples, it can be seen that the catalyst prepared by the preparation method provided by the present invention has high catalytic activity and stability, and exhibits an ultra-long life in the process of hydrogenation of liquid organic matter, and has good industrial applicability. In addition, the catalyst can be applied to a wide range of reaction conditions, and the mass hydrogen storage rate can reach 5.9wt% in the reaction.

[0130] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a catalyst for hydrogenating an organic liquid hydrogen storage medium, comprising: (1) preparing a mixed solution containing a first active metal source, an ammonium salt and an alkali; (2) mixing the mixed solution with an alumina carrier; (3) subjecting the product obtained in step (2) to hydrothermal crystallization, followed by drying and first calcination to obtain a catalyst intermediate; The conditions of the hydrothermal crystallization include: temperature of 80-150°C and time of 24-72h; (4) loading a second active metal onto the catalyst intermediate by an impregnation method, and then performing a second calcination; (5) subjecting the second calcined product to a reduction treatment under a reducing atmosphere; Wherein, the first active metal is selected from nickel and / or cobalt, and the second active metal is selected from at least one of gallium, indium and tin.

2. The preparation method according to claim 1, wherein The ammonium salt is selected from ammonium chloride and / or ammonium nitrate, and the base is urea; The molar ratio of the ammonium salt to the base is 1.5-2.5:1; The mixed solution also contains a solvent, and the solvent is water; In the mixed solution, the concentration of the first active metal source is 0.05-0.5 mol / L; The molar ratio of the base to the metal element in the first active metal source is (2-20):

1.

3. The preparation method according to claim 1 or 2, wherein The mixing in step (2) is carried out in a coating machine at a rotation speed of 40-100 rpm and a mixing time of 2-4 hours; The mass ratio of the first active metal in the mixed solution to the alumina support is (5-25):100; The alumina carrier is a shaped carrier, and the shape of the alumina carrier is at least one of a columnar shape, a cloverleaf shape, a toothed ball shape and a spherical shape.

4. The preparation method according to claim 1, wherein The hydrothermal crystallization is carried out under closed conditions, and the conditions of the hydrothermal crystallization include: temperature of 90-140° C. and time of 36-48 hours.

5. The preparation method according to claim 1, wherein The first calcination is carried out in the presence of oxygen; The temperature of the first calcination is 350-650° C., and the time is 1-10 hours.

6. The preparation method according to claim 1, wherein In step (4), the method of loading the second active metal onto the catalyst intermediate by impregnation includes: contacting a solution containing a soluble compound of the second active metal with the catalyst intermediate; In the solution containing the soluble compound of the second active metal, the concentration of the soluble compound of the second active metal calculated as the metal element is 2-18 wt %; The mass ratio of the loading amount of the second active metal to the first active metal in the catalyst intermediate is (0.1-0.6): 1; The second calcination is carried out in the presence of oxygen, the temperature of the second calcination is 400-600° C., and the time is 3-8 hours.

7. The preparation method according to claim 1, wherein The reducing atmosphere is a hydrogen-containing atmosphere, and the concentration of hydrogen in the hydrogen-containing atmosphere is 5-100 vol%; The temperature of the reduction treatment is 500-800° C., and the reduction time is 2-8 hours.

8. The preparation method according to claim 1, wherein The amounts of the first active metal source, the second active metal and the alumina carrier are such that, based on the total amount of the prepared catalyst, the content of the alumina carrier is 70-98wt%, calculated as elements, the content of the first active metal is 3-20wt%, the content of the second active metal is 0.5-11wt%, and the sum of all components is 100%.

9. Use of the catalyst prepared by the method for preparing the catalyst for hydrogenation of organic liquid hydrogen storage medium according to any one of claims 1 to 8 in organic liquid hydrogen storage.

10. A method for hydrogenating dibenzyltoluene, comprising: contacting dibenzyltoluene with a hydrogenation catalyst in the presence of hydrogen under hydrogenation reaction conditions; Wherein, the hydrogenation catalyst is a catalyst prepared by the method for preparing a catalyst for hydrogenation of an organic liquid hydrogen storage medium as described in any one of claims 1 to 8.

11. The hydrogenation method according to claim 10, wherein: The hydrogenation reaction conditions include: temperature of 120-180°C, pressure of 6-14 MPa, volume ratio of dibenzyltoluene to hydrogen of 1:(2000-4000), volume space velocity of dibenzyltoluene of 0.02-0.1h -1 .

Citation Information

Patent Citations

  • Supported nickel-based alloy catalyst as well as preparation method and application thereof

    CN109675569A

  • Supported CoxMy intermetallic compound catalyst as well as preparation and use methods thereof

    CN113477257A